2017
DOI: 10.1111/1756-185x.12996
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and contraceptive use in patients with systemic lupus Erythematosus, rheumatoid arthritis and women without a chronic illness: a comparative study

Abstract: More pregnancies occur in SLE than in RA after diagnosis of illness. Unplanned pregnancies and adverse pregnancy outcomes need to be addressed more in SLE than in RA or in WNCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…Nevertheless, methodological flaws were still existent. First, the sample sizes of some studies were small [15, 22]. The diagnosis criteria for APOs including GDM were obscure [14, 15, 22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, methodological flaws were still existent. First, the sample sizes of some studies were small [15, 22]. The diagnosis criteria for APOs including GDM were obscure [14, 15, 22].…”
Section: Resultsmentioning
confidence: 99%
“…Present studies indicated that SLE pregnancy is associated with elevated risk of GDM [10]. However, studies also reported that the GDM risk of SLE patients was not significant increased [9, 14, 15]. Besides, whether there are specific risk factors influencing GDM incidence in SLE patients is also doubtful.…”
Section: Introductionmentioning
confidence: 99%
“…Galappathy et al have reported an approximately 45% live birth rate in similar settings. 19 Appropriate contraceptive methods had been advised to all patients to avoid unwanted pregnancy, especially to prevent any possible deterioration of maternal condition due to the medical disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Bir olgu doğumdan iki ay sonra hastalığın alevlenmesi ve kardiyak tutulum neticesinde kaybedildi. Daha önceki çalışmalarda hastalığın gebelik sırasında alevlenmesi için %13-33 arasında oranlar bildirilmiştir (21) . Oranların faklı olması çalışmalar arasında hastalık aktivasyonunun tanımındaki farklılıklardan ya da profilaktik kortikosteroid kullanılıp kullanılmaması ile ilgili olabilir.…”
Section: Gereç Ve Yöntemlerunclassified